(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Ecological studies were carried out to ascertain the niche of latex-producing plants in the different vegetation belts of Northern Nigeria considering anthropogenic activities as a factor. Global Positioning System (GPS) and Stratified random sampling were used to locate towns for data collection. Twenty (20) plots of 15 m x 20 m (300 m2) quadrat size were considered, 5 plots from each vegetation belt of Southern Guinea Savanna (SGS), Northern Guinea Savanna (NGS), Sudan Savanna (SS) and Montane Vegetation (MV). Also, a quadrat size of 1 m x 1 m was placed 4 times in each of the 20 plots to enable the counting of forbs and grasses. The total latex-producing plants available in each of the vegetation belt revealed that Southern Guinea savanna had 6.57%, Northern Guinea savanna had 3.76%, Sudan savanna had 9.33% and Montane vegetation had 20.14% of the total number of individual plant species of 70, 53, 30 and 85 respectively collected in the each vegetation belt. Ten (10) families collected during the work were noted to produce latex namely, Aloeceae, Sapotaceae, Cohlospermaceae, Euphorbiaceae, Moraceae, Convolvulaceae, Meliaceae, Asclepiaceae, Cactaceae and Apotaceae. Thirty three (33) of the plant species collected were latex-producing plants, while 109 plant species were non-latex producing plant species. The diversity of latex-producing plants decreases to the North probably because of the increase in the open grazing and other human activities